Validity and reliability of 5 Hz GPS for measurement of non-linear cycling distance and velocity - Hurst, H. T.; Sinclair, J. (International Journal of Sports Science and Engineering, 2013)
This study aimed to determine the validity and reliability of a 5 Hz GPS system for recording distance and velocity during non-linear cycling activity. One trained male cyclist (age 37 yrs; stature 172.4 cm; body mass 74.2 kg) took part in the study. Two non-differential GPS units (Minimax X3, Catapult) were attached securely into the rear pocket of a cycling shirt at approximately the T11-12 vertebrae. The participant performed 3 laps at each velocity of 10, 20 and 30 km.h-1 on a tarmac track. GPS distance was contrasted to that recorded by a calibrated trundle wheel and cycle computer (COMP) (S710, Polar), whilst GPS velocity was compared simultaneously with the COMP. GPS and COMP velocities were strongly correlated at 10 km.h-1 (r = .997, R2 = .993, p<05) and 30 km.h-1 (r = .955, R2 = .913, p<05) and moderately correlated at 20 km.h-1 (r = .539, R2 = .290, p>05). No significant differences were revealed for distance between trundle wheel, GPS and COMP (p>.05, .2 = .152) or GPS distance at different velocities (p>.05, .2 = .238). Overall intra and inter-unit reliability for distance were 1.83 % and .90 % respectively, whilst overall intra and inter-unit reliability for velocity were 2.53 % and 2.03 % respectively. This study showed GPS provides a valid and reliable means of monitoring distance and velocity during non-linear cycling activity across a range of velocities.